Attitude of medical students towards learning communication skills - Haveri, Sheela P; NM, Sebastian; Nath, Arya S (International Journal Of Community Medicine And Public Health, 2017)
Background: The need for developing Communication skills among medical students is now gaining emphasis. Ability to communicate with patients is one of the competencies required for all doctors as competent health providers. The Objective of this study is to conduct the attitude of medical students towards learning communication skills and to identify the relationship of demographic characteristics to such an attitude. Methods:The study is conducted in MES Medical college in Kerala, India among 1st to final year students using a validated questionnaire namely Communication skills Attitude scale having 13 +13 questions to get positive and negative attitudes. Results: The study showed higher positive attitude score of 53 against negative score of 27. Female gender and higher mother’s education were associated with more positive scores. Conclusions:Over all students in the study have more positive attitude towards learning communication skills, girls having more positive attitude than boys and mothers’ educational status positively influences the attitude.